Prosocial intentions towards religious ingroup and outgroup members among adolescents from public and religious schools - Azzahra, Farah Aisyah; Ampuni, Sutarimah (Indigenous, 2021)
Abstract. Prosocial behavior is a very important component in harmonious social relationships, especially within a diverse community such as Indonesia. Public and religion-based schools provide different opportunities for students in terms of interaction with peers from different religions, and in turn may affect attitudes toward ingroup and outgroup religious members. This study compared prosocial intentions towards religion-based ingroup and outgroup peer members in adolescents from heterogeneous (public) schools and homogenous (Islamic) schools. Participants were 220 Muslim middle school studentsaged 11-15 years, who attended public schools (N= 130; M=48, F=82) and religious schools (N=90; M=46, F=44). They were recruited through snowball sampling and convenience sampling. This research is a quasi-experimental study, by using the Scenario-based Prosocial Intention Questionnaire (SBPIQ) to measure prosocial intentions, which was modified to include manipulations on the targets of prosocial intention. Two-way mixed ANOVA results showed that the level of prosocial intention was highest toward the ingroup target (M=3,411; SD=0,392), followed by those toward the outgroup (M=3,357; SD=0,403) and neutral targets (M=3,234; SD=0,411). Furthermore, prosocial intentions towards ingroup, outgroup, and neutral targets were all higher in students from public schools. Theseresults implied that there were biases in students’ prosocial behaviors toward ingroup/outgroup religious members. It is crucial for both public and Islamic schools to facilitate positive interactions with members of other religious group in order to overcome these biases.Keywords: ingroup-outgroup, interreligious, prosocial intention, prosocial behavior, adolescents, homogeneous/heterogeneous school